Mga kagamitang panturo sa isahang pag-aaral sa pakikinig sa ikalimang baitang ng mababang paaralan sa kaligirang pangalawang wika - Gines, Adelaida C. 1949- (1977)
This "special problem" attempted to design and develop a set of aural discourse materials in teaching Pilipino as the second language in Grade V. This study was concerned with two phases of the materials design, namely, the design and development phases. The design phase includes the setting out of the rationale which discussed the common weaknesses observable in the currently available learning materials in Pilipino for Grade V. As a consequence, some promising concepts were offered to overcome such weaknesses and failures. This study has provided materials writers some insights into the process of materials design and development.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Teaching -- Aids and devices; Pilipino -- Instruction and study